Frailty in the context of COVID-19 pandemic: A life-threatening condition - Fernandes, Alan L.; Pereira, Rosa M. R. (Frontiers in Medicine, 2022)
The pandemic outbreak of coronavirus disease 2019 (COVID-19) has caused emerging challenges for healthcare systems regarding the assistance to the older adult population which, added to the increased life expectancy, may be exposing frail older adults to an increased risk of unfavorable health outcomes. Frailty has a pathogenesis of multifactorial etiology and is defined as a condition characterized by progressive decline in physiological function, weakness, decreased strength, and reduced resilience to stressors, leading to vulnerability and an increased risk of fractures, falls, institutionalization, and death. In the context of COVID-19, frail older adults accounted for approximately 51% of hospitalized patients with confirmed cases and elevated risk of mortality in-hospital. In addition, frailty may be associated with recent excess mortality reported by the World Health Organization (WHO) in terms of the full death toll associated directly (due to the disease) or indirectly (due to the pandemic’s impact on health systems and society) to COVID-19. Therefore, this mini review aimed to provide a summarized discussion from meta-analyses data regarding the impact of frailty in community-dwelling older adults hospitalized with COVID-19 on short-term mortality risk.